The excavation - Jackson, Adam; Warren, Graeme; MacSween, Ann; Lawson, John; Duffy, Paul (Scottish Archaeological Internet Reports, 2009)
This chapter presents aims and methods, describes the setting and gives a brief history of the site. Archaeological description of the remains is followed by specialist reports on chipped stone, coarse stone, prehistoric, medieval and later pottery and human skeletal remains. Two radiocarbon dates were obtained.